2017
DOI: 10.1001/jamainternmed.2017.1313
|View full text |Cite
|
Sign up to set email alerts
|

Publication and Reporting of the Results of Postmarket Studies for Drugs Required by the US Food and Drug Administration, 2009 to 2013

Abstract: We thank Renee Gennarelli, MS, for extra statistical support; she was not compensated for her contributions.1. Thavendiranathan P, Bagai A, Ebidia A, Detsky AS, Choudhry NK. Do blood tests cause anemia in hospitalized patients? the effect of diagnostic phlebotomy on hemoglobin and hematocrit levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…Our finding that about three quarters of the postmarket clinical trials had either reported results or were published is consistent with a recent study by the FDA, which showed that nearly two thirds of postmarket drug interventional clinical trials and other trials designated as “fulfilled” were published in either the scientific literature or on the ClinicalTrials.gov website 16. However, only 55.5% of postmarket studies for which publication would be expected were published in peer-reviewed medical journals.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding that about three quarters of the postmarket clinical trials had either reported results or were published is consistent with a recent study by the FDA, which showed that nearly two thirds of postmarket drug interventional clinical trials and other trials designated as “fulfilled” were published in either the scientific literature or on the ClinicalTrials.gov website 16. However, only 55.5% of postmarket studies for which publication would be expected were published in peer-reviewed medical journals.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, the FDA might need to provide additional clarity to sponsors about which trials need to be registered and when results need to be reported. Furthermore, new regulations might be needed to ensure that the results from postmarket studies that are of most interest to the clinical community, including prospective cohort studies and registries, are publicly disseminated 16. Alternatively, sponsors can also voluntarily take on part of the responsibility and commit to greater registration and results dissemination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have focused exclusively on the characteristics [7], completion [8, 9], and dissemination of postmarketing requirements [7, 10, 11]. For instance, among the 110 new drugs and biologics approved by FDA between 2009 and 2012, 97 (88.2%) had at least one postmarketing requirement at the time of approval (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, nearly one quarter of PMR results are either not reported on ClinicalTrials.gov or published in the peer-reviewed literature. 3,4 Therefore, our objective was to characterize the timeliness of PMR studies, comparing FDAestablished timeliness milestones with expected completion times outlined on ClinicalTrials.gov.…”
Section: Introductionmentioning
confidence: 99%